2011
DOI: 10.1007/s12094-011-0713-y
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal therapy for adult Wilms’ tumour: an experience from one centre

Abstract: The results of this report suggest that histological anaplasia might be an adverse prognostic factor for AWT. Proper application of the diagnostic and therapeutic regimens established for children may improve the prognosis of adult patients with WT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Although adult WTs have been relatively well described in pathology studies (3,4), imaging data are scanty. However, patients with adult WT have a different prognosis from other renal cell carcinoma (RCC) subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Although adult WTs have been relatively well described in pathology studies (3,4), imaging data are scanty. However, patients with adult WT have a different prognosis from other renal cell carcinoma (RCC) subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Based on this, it is concluded that adults can be cured by paediatric multimodality protocols. [12] National Wilms' Tumour Study (NWTS) and other studies have recommended multimodal approach for the disease with surgery, chemotherapy (Vincristine, actinomycin D and doxorubicin) for 18 to 27 weeks and tumour bed irradiation 10.8 Gy for stage 3 and 4 disease. Additionally, chest irradiation 12 Gy for stage 4.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there was no Wilms tumor epidemiological investigation in Indonesia. [2] Multimodal therapies are used to treat Wilms tumor patients in the majority of cases [3,4]. Surgery, chemotherapy, and radiation are administered in stages, which can boost 5-year survival rates by up to 90%.…”
Section: Introductionmentioning
confidence: 99%